Gandhi, tribes and rural development - National Seminar on 'Gandhi: Tribal and Rural Development' (2019 : Udaipur, Rajasthan, India); Bagchi, Tilak; Anthropological Survey of India. Western Regional Centre (Jaipur : Rawat Publications, 2023)
Contributed papers presented at National Seminar on 'Gandhi: Tribal and Rural Development', organized by Anthropological Survey of India, Western Regional Centre, held at Udaipur on January 29-30, 2019.
1. Introduction / Tilak Bagchi -- 2. Gandhian model of development and his views on modernity and post-modernity in India / S.L. Sharma -- 3. Mahatma Gandhi: a great visionary leader / B.P. Bhatnagar -- 4. Gandhi on protest and reconstruction of society / N.K. Bhargava and P.C. Jain -- 5. Gandhi's rural development perspective: present day scenario in rural and tribal areas of India / Debashis Debnath -- 6. Mahatma Gandhi and tribes of India / R.P. Mitra -- 7. Impact of Gandhi on tribes of India: the subliminal, direct and coordinate influences / Nishant Gokhale -- 8. Gandhian model of development and rights of the tribes in India / H.S. Chandalia -- 9. Gandhian concept of rural development / Brij Kishore Sharma -- 10. Gandhian vision on rural-tribal development and its importance on Swachh Bharat Movement / Ashok Kumar Sahani -- 11. Gandhian philosophy in the Indian economics and rural milieu / K.M. Sinha Roy -- 12. Renewing Gandhi's thoughts on rural entrepreneurship development: reference to possibilities of mushroom farming in India / Arabinda Mitra, Pijush K. Ghosh and Palash C. Coomar -- 13. Role of Gandhian organizations in rural reconstruction: a case study of Paschim Medinipur District in West Bengal / Tuhin Kanti Das -- 14. Gandhian perspective on rural development / Anju Beniwal -- 15. Relevance of Gandhi's educational thoughts in the present times / Shruti Tandon -- 16. Gandhi as people's leader in national movement / Pritish Chaudhuri.
Copyright: Anthropological Survey of India, Government of India, Kolkata.
Includes bibliographical references and index.
Keywords: Gandhi, Mahatma -- 1869-1948 -- Mahatma, -- Political and social views -- Congresses; Rural development -- India -- Congresses; Tribes -- Government policy -- India -- Congresses; Conference papers and proceedings